Sociological dimension of international relations - Kochetkov, Vladimir V. (Journal of the Belarusian State University. Sociology, 2019)
The article describes the history of the emergence and development of the sociology of international relations (SIR) as an independent science from the moment of its appearance to the present day. Special attention is paid to the contribution of Russian scientists to the development of the sociology of international relations. It is shown that the prehistory of the Russian school of sociology of international relations dates back to the 19th century in the works of N. Kareev, L. Mechnikov, and the term «sociology of international relations» was first introduced into scientific circulation by the Russian researcher V. Klyuchnikov in 1922. Different points of view on the sociology of international relations are considered. The authorʼs position is that it is impossible to deny the study of world political realities from the standpoint of sociology, since society can be international in the same way as the national one. A comparative analysis of the main provisions of national (Russian, Chinese and Western) schools of international relations was conducted. Special attention is paid to the domestic school of sociology of international relations. Three major Russian tradition in the study of international relations – Westernism, Great power nationalism and Treterimstvo are characterized. It is concluded that under the crisis of the Westphalian system, increasing chaos and enter of new non-state actors on the international arena, international relations are increasingly sociological.